Clinical perspective: caesarean hysterectomy for placenta accreta spectrum and role of pelvic packing - David, Liji; Abraham, Anuja; Regi, Annie (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Caesarean hysterectomy (CH) is considered the gold standard for management of morbidly adherent placenta, now termed as placenta accreta spectrum (PAS). If bleeding is not controlled following removal of uterus, it is sometimes necessary to pack the pelvis and continue monitoring with correction of bleeding and physiological parameters in operating room and intensive care unit. This now comes under the damage control approach, being driven primarily by abnormal physiology rather than anatomical reconstruction. The pelvic packs are removed after about 48 hours. This retrospective study was done in patients with antenatal diagnosis of PAS who required CH, comparing those who required pelvic packing with those who did not. The variables compared were pre-operative (clinical and radiological), intra-operative (duration of surgery, blood loss and transfusion requirements of whole blood and blood products), and the final histopathological diagnosis. Outcome variables in terms of duration of hospital stay, re-admissions, re-laparotomy and complications were also compared. Over two years, three of eight patients with PAS required pelvic packing following CH. There were no differences between the two patient groups with any of the predictor variables or outcomes other than requirement of blood products. This suggests pelvic packing is a safe and efficacious procedure in intractable haemorrhage following CH for PAS. Pelvic packing needs greater awareness amongst obstetricians as the incidence of PAS is likely to increase.